1977
DOI: 10.1177/25.7.330726
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted karyotyping with human interaction.

Abstract: A system for machine assisted karyotyping and chromosome analysis has been developed. The system uses a drum-or TV-scanner as input device, runs provisionally in 32 K memory, and also allows human interaction on several stages. The accuracy with which banded chromosomes are karyotyped I Supported by F. G. W. 0. Grant 20. 492. 2 Aspirant National Foundation of Scientific Research. 3 Bursaal I. W. 0. N. L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Three data bases were used in this study (Table 11, in each of which correct classification into one of the 24 human chromosome classes (1-22, X, Y) was provided by experienced cytogeneticists to permit evaluation of the performance of automatic classification. Various studies have shown that even experienced cytogeneticists occasionally disagree about the classification of normal chromosomes, the extent of the disagreement having being variously measured between 0.1% (19) and 1.7% (38) when classifying photographs of complete G-banded metaphases and 1% after the correction stage of interactive rnachine karyotyping (22). We must therefore realistically expect that there is a similarly small error rate remaining in the data bases that we have used, but that it is insignificant compared with the error rates following automatic classification, which we present below.…”
Section: Materials and Methods Data Basesmentioning
confidence: 99%
“…Three data bases were used in this study (Table 11, in each of which correct classification into one of the 24 human chromosome classes (1-22, X, Y) was provided by experienced cytogeneticists to permit evaluation of the performance of automatic classification. Various studies have shown that even experienced cytogeneticists occasionally disagree about the classification of normal chromosomes, the extent of the disagreement having being variously measured between 0.1% (19) and 1.7% (38) when classifying photographs of complete G-banded metaphases and 1% after the correction stage of interactive rnachine karyotyping (22). We must therefore realistically expect that there is a similarly small error rate remaining in the data bases that we have used, but that it is insignificant compared with the error rates following automatic classification, which we present below.…”
Section: Materials and Methods Data Basesmentioning
confidence: 99%
“…Zimmerman et al (1986) measured a mean person-to-person disagreement of about 1.7% among several pairs of trained observers classifying human G-banded chromosomes in melaphase photographs. Lundsteen et al (1976) reported a much lower error rate o f 0.1% under similar circumstances, and Oosterlinck et al (1977) reported a final error of I % alter operator interaction in an experimental karyotyping machine. One would expect similar or poorer concordance with mouse melaphases.…”
Section: C¡ossification Accuracymentioning
confidence: 99%
“…Thresholding works for the chromosome images because chromosomes tend to appear in bright intensities compared to the background of the image. [31][32][33] Common global thresholding techniques which have been used to segment the chromosome images include Otsu's thresholding and Kapur's thresholding. Otsu's thresholding extracts the chromosomes from the image by minimizing the intra-class variance of the pixels within each cluster.…”
Section: Thresholding-based Chromosome Segmentationmentioning
confidence: 99%